The knowledge manager's handbook : a step-by-step guide to embedding effective knowledge management in your organization - Milton, N. J.; Lambe, Patrick, 1960- (Kogan Page Limited, 2020)
"The way an organization manages and disseminates its knowledge is key to informed business decision-making, effectiveness and competitive edge. The Knowledge Manager's Handbook takes you step by step through the processes needed to define and embed an effective knowledge management framework within an organization. This second edition now includes clear guidance on the best practice requirements from the first ever internationally recognised standard for knowledge management, ISO 30401, as well as content on the impact of AI and data analytics. Nick Milton and Patrick Lambe work through each stage of creating and implementing a knowledge management framework for an organization's specific needs, based around the four essential aspects of knowledge management: people, processes, technologies and governance. With updated international case studies from organizations of all sizes and sectors, along with user-friendly templates and checklists to help implement effective knowledge management procedures, The Knowledge Manager's Handbook is the end-to-end guide to making a sustainable change in the knowledge management culture"- Resumé vydavatel
Keywords: znalostní management; knowledge management; elektronické knihy; příručky; electronic books; handbooks and manuals